An examination of the epistemology contained in Bernard Lonergan's Insight as a potential integrative frame for interreligious dialogue, with particular reference to Karl Rahner's Foundations of Christian Faith and Nāgarjuna's Mūlamadhyamakakārikā - Robinson, John (Irish School of Ecumenics, 2014)
This thesis sought to examine the viability of the epistemology proposed by Bernard Lonergan in his seminal work Insight, particularly with regard to its possible application in the field of interreligious dialogue. This enquiry was prompted by an awareness of the epistemological questions raised by the various dialogues taking place between different religions, and it was in light of this that Lonergan’s claim to comprehensiveness in his epistemology was examined.
Keywords: Religions, Theology & Ecumenics Ph.D.; Ph.D. Trinity College Dublin